Effect of Perioperative Systemic Dexamethasone on Pain, Edema, and Trismus in Mandibular Fracture Surgery: A Randomized Trial. Issue 8 (6th November 2021) - Oksa, Marko; Haapanen, Aleksi; Furuholm, Jussi; Thorén, Hanna; Snäll, Johanna
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The authors' aim was to evaluate the effect of perioperative systemic dexamethasone (DXM) administration on postoperative pain, edema, and trismus in mandibular fracture patients. The authors conducted a prospective randomized study of 45 patients with one or 2 noncomminuted fractures of the dentate part of the mandible. All patients underwent surgery for intraoral miniplate fixation. Patients in the study group were given a total of 30 mg DXM, while patients in the control group received neither DXM nor placebo. Only paracetamol and opioids were served as analgesics. Pain severity was assessed using the visual analog scale. The effect in facial swelling was measured in centimeters and analyzed as percentage change. Trismus was evaluated as the difference in maximal mouth opening by measuring interincisal distance in millimeters. The Mann-Whitney U test was applied to determine the statistical significance of differences between the groups. Thirty-four patients were included in the statistical analysis. The visual analog scale score was significantly lower in the study group than in the control group at 18 hours postoperatively ( P  = 0.033). Significant differences in edema or trismus were not found postoperatively between the DXM and control groups. In conclusion, perioperative DXM decreases postoperative pain in mandibular fracture patients when nonsteroidal anti-inflammatory drugs are not used, but it does not seem to be effective in reducing edema or trismus.